MINORS AND THEIR INCAPACITY TO CONTRACT: A REVISIT (UUM Journal of Legal Studies, 2023)
Given the exposure to today's easy-to-know information, children should seemingly become mature faster than their predecessors, and therefore better informed even at a tender age. However, it remains to be seen whether fixingthe age of 18 forminors or children to enter into contracts is relevant. This paper focuses on contract law; it examines the age of majority and the legal implications of contracts entered into by minors. To a certain extent, this paper examines the issue by making comparisons between Malaysian and English law. The findings derived imply that the determination of the age of majority needs to be compatible with the capacity of minors and current realities. This determination must be premised on a fair balance between protecting minors' welfare and the interest of those who have attained the age of majority.